Dispositionalism: a study on properties - Raimondi, Andrea (2019)
In this thesis I offer a study of a metaphysical theory that has acquired popularity in recent years: dispositionalism. Dispositionalism is a non-reductive theory of physical modality, according to which the pattern of instantiation within the four-dimensional manifold is determined and explained by the modal nature of properties. I defend a version of dispositionalism based on the ontology of platonic universals, and I argue that dispositionalists must be platonic dispositionalists if they are to be dispositionalists at all.